Electrochemical surface nanopatterning using microspheres and aryldiazonium - Corgier, Benjamin P (Langmuir : the ACS journal of surfaces and colloids, 2010)
A multistep procedure to prepare heterogeneous structured surfaces with contrasted chemical functionalities at the nanometer scale is presented. Aryldiazonium cations are used for the nanopatterning of electrodes to create hybrid surfaces. The nanopatterning procedure involves the auto-organization of a polystyrene (PS) beads layer at gold or glassy carbon electrode surfaces. The deposited beads layer permits masking of a fraction of the surface from a first aryldiazonium electrografting process. By subsequent removal of the PS beads, the ungrafted surface areas become available for either another aryl diazonium electrografting or a metal electrodeposition, leading to hybrid nanostructured surfaces